Rock engineering design properties and applications of sound level - Vardhan, Harsha; Bayar, Rajesh Kumar (CRC Press, 2014)
Being knowledgeable about rock properties is vital to being effective in the design of blasts in mines, quarries and other construction projects. Without proper knowledge, the energy released during blasting can be underutilized, harm the environment, and may escalate costs. Rock Engineering Design: Properties and Applications of Sound Level aids scientists and practicing engineers in determining rock properties in a quick and precise way. It presents the basic concepts and principles on which sound level can be used in solving rock engineering design problems